A phase I study evaluating the safety and pharmacokinetics of weekly paclitaxel and carboplatin in relapsed ovarian cancer. Issue 2 (1st February 2007) - Leiser, A. L.; Maluf, F. C.; Chi, D. S.; Sabbatini, P.; Hensley, M. L.; Schwartz, L.; Venkatraman, E.; Spriggs, D.; Aghajanian, C.
Abstract : This phase I study sought to determine the toxicity profile, pharmacokinetics, and antitumor activity of giving carboplatin every 3 weeks and paclitaxel weekly in patients with relapsed ovarian cancer. Eligible patients with relapsed epithelial ovarian cancer and prior treatment with platinum- and paclitaxel-based therapy were treated with an escalating regimen of carboplatin (day 1) at an area under the curve (AUC) of 4–6 and 1-h infusions of paclitaxel (days 1, 8, and 15) at 50–80 mg/m 2 cycled at 3-week intervals. Pharmacokinetic studies were performed on the first day of cycles 1 and 2. All patients had a platinum-free interval of greater than 6 months from the most recent platinum treatment. A total of 77 cycles were administered to 16 patients, with a similar median number of cycles per patient at each dose level varying from 4.6 to 5.3. Febrile neutropenia and grade 4 thrombocytopenia were the dose-limiting toxicities at dose levels 3 and 4 after the third cycle, with no mucositis, nausea, vomiting, or peripheral neuropathy observed greater than grade 2. The maximum tolerated dose of carboplatin was an AUC of 5 and 80 mg/m 2 for paclitaxel. Pharmacokinetic analysis showed a marginal statistical difference with regard to reduced systemic paclitaxel concentration after cycle 2 compared with cycle 1 ( P = 0.06). Of nine patients evaluable for a radiographic response, the response rate was 66.6% with a complete response of 33.3%. All five patients with nonmeasurable disease achieved a biochemical response. The combination of carboplatin given every 3 weeks at an AUC of 5 and 1-h weekly paclitaxel at 80 mg/m 2 is a feasible and reasonably well-tolerated regimen and may have significant antitumor activity in relapsed ovarian cancer patients.